Een coherente cartografie voor een geïntegreerd waterbeleid in Brussel - Tom Goosse; Kevin De Bondt; Guido Petrucci; Philippe Claeys (Brussels Studies)
Like many cities, Brussels faces increasing water issues like urbanization spreading and stresses on the water resources. Integrated Water Management (IWM) in urban planning tackles these problems focusing on the landscape features, but requires extensive cartographic data. Since 2010, different platforms offer cartographic data for the Brussels and Flemish regions, but these initiatives are independent and often not coherent. This article analyses the potentials and deficiencies of these cartographic data through two transboundary examples: the catchments of the Brussels area and the Molenbeek catchment. The article highlights how non-concordance and non-accessibility of the data constrain the application of IWM and other urban planning issues in transboundary areas.